2008
DOI: 10.1038/nmat2332
|View full text |Cite|
|
Sign up to set email alerts
|

Highly conductive ∼40-nm-long molecular wires assembled by stepwise incorporation of metal centres

Abstract: One of the main goals of molecular electronics is to achieve electronic functions from devices consisting of tailored organic molecules connecting two metal electrodes. The fabrication of nanometre-scale spaced electrodes still results in expensive, and often scarcely reproducible, devices. On the other hand, the 'conductance' of long organic molecules--generally dominated by the tunnelling mechanism--is very poor. Here, we show that by incorporating a large number of metal centres into rigid molecular backbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
265
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(290 citation statements)
references
References 34 publications
19
265
3
Order By: Relevance
“…Temperature-dependent transport with a small β-value has been associated with activated hopping between sites in both single molecules (35,36) and ensemble junctions (16,23), presumably governed by MarcusLevich kinetics. The low-V, high-T Arrhenius slopes of 150-300 meV listed in Table 1 are comparable to those reported for bulk polythiophene, e.g., 128-143 meV (37) and 280 meV (38), in which interchain charge transfer dominates transport (39,40).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature-dependent transport with a small β-value has been associated with activated hopping between sites in both single molecules (35,36) and ensemble junctions (16,23), presumably governed by MarcusLevich kinetics. The low-V, high-T Arrhenius slopes of 150-300 meV listed in Table 1 are comparable to those reported for bulk polythiophene, e.g., 128-143 meV (37) and 280 meV (38), in which interchain charge transfer dominates transport (39,40).…”
Section: Resultsmentioning
confidence: 99%
“…For this distance range, there is general agreement that the conductance scales exponentially with length, with an attenuation coefficient (β), defined as the slope of ln J vs. thickness (d), equal to 8 to 9 nm −1 for aliphatic molecules (3-6) and 2-3 nm −1 for aromatic molecules (7)(8)(9)(10)(11)(12)(13)(14). A few molecular electronic systems have been investigated beyond 5 nm (15,16), some of which exhibit a decrease in β to less than 1 nm −1 . Such small values of β are significant both practically (17,18) and fundamentally (19)(20)(21)(22), because they imply transport across distances much greater than the dimensions of single molecules and may enable complex molecular circuits.…”
mentioning
confidence: 92%
“…6 Rampi et al reported electrical measurements of such metal incorporated nanowires up to 40 nm in length with extremely low β values of 0.28 nm −1 (Fe II ) and 0.01 nm −1 (Co II ) implicating a multistep charge hopping process between the metal centres in the backbone. 7 Thus conductivity does not decrease significantly with length and depends on the metal atom. Wires up to 5 nm incorporating Zn porphyrins were also found to display very low attenuation factors (0.4 nm −1 ).…”
Section: Molecular Junctions With Metal Complexesmentioning
confidence: 96%
“…Monolayers of electroactive molecules on bulk metallic surfaces, in particular, Au and Pt have shown interesting behavior and some promising results [8][9][10]. The central key feature is to have electro/photoactive organic and organometallic fragments assembled onto these surfaces and study their charge conductivity [11][12][13][14][15] or eventually their electroluminescence in molecular junctions [16]. Different chemical functionality is required to assem-ble these molecules on the bulk surfaces through covalent and noncovalent interactions.…”
Section: Introductionmentioning
confidence: 99%